2023
DOI: 10.4252/wjsc.v15.i4.196
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of analgesic effect of mesenchymal stem cells in osteoarthritis pain

Abstract: Osteoarthritis (OA) is the most common musculoskeletal disease, and it is a major cause of pain, disability and health burden. Pain is the most common and bothersome presentation of OA, but its treatment is still suboptimal, due to the short-term action of employed analgesics and their poor adverse effect profile. Due to their regenerative and anti-inflammatory properties, mesenchymal stem cells (MSCs) have been extensively investigated as a potential therapy for OA, and numerous preclinical and clinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 102 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…In addition, synovial MSCs (SMSCs), embryonic stem cell-derived MSCs (ES-MSCs), and MSCs from other sources have also been studied as potential treatments for OA. In rats with OA, injection of ES-MSCs derived from embryos showed effects such as alleviating OA pain, protecting joint structures, and slowing OA progression [ 77 ]. Akgun et al used a combination of SMSCs (treatment group) and chondrocytes (control group) with a I/III collagen membrane to treat patients with knee joint cartilage defects.…”
Section: Application Of Mscs From Different Sources In Oa Therapymentioning
confidence: 99%
“…In addition, synovial MSCs (SMSCs), embryonic stem cell-derived MSCs (ES-MSCs), and MSCs from other sources have also been studied as potential treatments for OA. In rats with OA, injection of ES-MSCs derived from embryos showed effects such as alleviating OA pain, protecting joint structures, and slowing OA progression [ 77 ]. Akgun et al used a combination of SMSCs (treatment group) and chondrocytes (control group) with a I/III collagen membrane to treat patients with knee joint cartilage defects.…”
Section: Application Of Mscs From Different Sources In Oa Therapymentioning
confidence: 99%
“…7 More evidence has shown that intraarticular (IA) injection of MSCs from different sources could relieve pain and improve function in knee OA in preclinical models and clinical trials. 8 However, clinical application of MSCs transplantation is still limited by the low efficiency in oriented differentiation into chondrocyte because of the inflammatory microenvironments. 9 It was reported that the osteoarthritic synovial fluid, containing a large amount of inflammatory synovial macrophages and proinflammatory factors, inhibited the chondrogenesis of MSCs and downregulated the expression of chondrogenic genes (Col2 and ACAN).…”
mentioning
confidence: 99%
“…It has been reported that transplanted MSCs could migrate to the lesioned regions and differentiate into chondrocytes, thereby leading to cartilage regeneration . More evidence has shown that intra-articular (IA) injection of MSCs from different sources could relieve pain and improve function in knee OA in preclinical models and clinical trials . However, clinical application of MSCs transplantation is still limited by the low efficiency in oriented differentiation into chondrocyte because of the inflammatory microenvironments .…”
mentioning
confidence: 99%
“… 19 , 20 , 21 The definitive pathways of cartilage regeneration induced by orthobiologic therapies are still discussed controversially and are a matter of ongoing research. 3 , 22 , 23 Nevertheless, recent studies have pointed out promising and easy-to-handle techniques to harness the beneficial effects of regenerative orthobiologic therapeutics. 9 , 23 , 24 , 25 In particular, abdominal adipose tissue has been recognized as a potential source of ASCs.…”
mentioning
confidence: 99%
“… 3 , 22 , 23 Nevertheless, recent studies have pointed out promising and easy-to-handle techniques to harness the beneficial effects of regenerative orthobiologic therapeutics. 9 , 23 , 24 , 25 In particular, abdominal adipose tissue has been recognized as a potential source of ASCs. 26 …”
mentioning
confidence: 99%